2013
DOI: 10.1097/brs.0b013e31829ff095
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Versus Nonsurgical Treatment of Cervical Radiculopathy

Abstract: Study DesignProspective randomized controlled trial. ObjectiveTo study the outcome of anterior cervical decompression and fusion (ACDF) combined with a structured physiotherapy program compared to the same physiotherapy program alone for patients with cervical radiculopathy. Summary of Background DataKnowledge concerning the effects of interventions for patients with cervical radiculopathy is scarce due to a lack of randomized studies. Methods63 patients were randomized to surgery with postoperative physiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 19 publications
1
66
0
1
Order By: Relevance
“…Neurological signs were greatly reduced after surgery-patients suffered from significantly less arm pain, pareses and paresthesias. This is in line with previously published reports that found the surgery effective for the treatment of cervical radiculopathy in terms of pain reduction, disability, weakness, and numbness [23,24,25,26]. Also, significantly lower neck pain was reported after the intervention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Neurological signs were greatly reduced after surgery-patients suffered from significantly less arm pain, pareses and paresthesias. This is in line with previously published reports that found the surgery effective for the treatment of cervical radiculopathy in terms of pain reduction, disability, weakness, and numbness [23,24,25,26]. Also, significantly lower neck pain was reported after the intervention.…”
Section: Discussionsupporting
confidence: 92%
“…However, when neck pain is associated with radiculo- or myelopathy, surgical intervention has been reported to alleviate the symptoms [25,26]. Engquist et al [26] recently published a randomized controlled trial comparing surgery plus physiotherapy to physiotherapy alone. The results suggested that the combined approach is superior to physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, some suffer from complications following surgery and require additional surgery due to severe pain. According to the latest research, surgery resulted in the same outcomes as those of physical therapy without surgery after two years in terms NDI and arm pain [10].…”
Section: Minimally Invasive Widening Of the Facet Joints In Cervical mentioning
confidence: 84%
“…Outcome of surgical management for cervical disc herniation has shown a success rate of 66 to 98% [8]. ACDF has demonstrated good results in terms of pain relief and patient satisfaction [9]. Its success rate has been reported to achieve good or excellent outcome in 93% [10].…”
Section: Introductionmentioning
confidence: 99%